1982
DOI: 10.1017/s0021859600041241
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Rhizobium in the phyllosphere of crop plants in nitrogen-free sand culture

Abstract: Soya bean, mung bean, Bengal gram and lentil grown in nitrogenless sand culture and sprayed with suspensions of different strains of Rhizobium showed increases in dry weight, chlorophyll and N-content. In a few cases the performance of Rhizobium applied to the phyllosphere was almost as good as a seed inoculation treatment. The beneficial effect of spraying Rhizobium strains was independent of the specificity of cross-inoculation groups. Nitrogenase activity as indicated by acetylene reduction by the Rhizobiit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

1982
1982
2017
2017

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
0
3
0
1
Order By: Relevance
“…As in the case of nitrogen-free sand culture experiments described in the previous paper (Nandi et al 1982) the field experiments showed that the growth attributes studied were improved with a considerable increase in yield. The increases observed are independent of the affiliation of the Rhizobium strain to any specific cross-inoculation groups or effectiveness for nodulation.…”
Section: Discussionmentioning
confidence: 57%
“…As in the case of nitrogen-free sand culture experiments described in the previous paper (Nandi et al 1982) the field experiments showed that the growth attributes studied were improved with a considerable increase in yield. The increases observed are independent of the affiliation of the Rhizobium strain to any specific cross-inoculation groups or effectiveness for nodulation.…”
Section: Discussionmentioning
confidence: 57%
“…The improvement observed is equivalent to what is usually found with 40-60 kg N/ha. Sengupta et al (1982a), Sengupta & Sen (1982) obtained more impressive results with the Klebsiella strains KUPBR 2 and KUP 4 . Since we have used the same strains it appears that the efficiency of the strain may have decreased during maintenance in the laboratory in the intervening period.…”
Section: Discussionmentioning
confidence: 95%
“…chroococcum, Az. vinelandii OP and two N 2 -fixing phyllosphere iso-In a series of publications Sengupta & Sen (1976), i a t e s o f unknown identity were also included in Sengupta, Sen & Sen (1978), Sengupta et al (1981), t hi s study Sengupta, Nandi & Sen (1982a), Sen (1982) and Nandi, Sengupta & Sen (1983)…”
Section: Introductionmentioning
confidence: 99%
“…Já foi demonstrado, em estudo de campo, que a FBN por rizóbios pode ser importante para as plantas, mesmo que ocorra de forma epifítica, em locais distantes da raíz (Nandi et al, 1982), e que algumas linhagens de Rhizobium poderiam fixar nitrogênio assimbioticamente (Oliveira-Longatti et al, 2013). No entanto, poucos estudos reportam essa capacidade de Rhizobia fixar nitrogênio assimbioticamente, e sua relevância em ecossistemas naturais.…”
Section: Discussionunclassified